Effect of various hepatectomy procedures on circulating tumor cells in postoperative patients: a case-matched comparative study - Lei, YongRong; Wang, XiShu; Tian, YiChen; Xu, Rong; Pei, Jun; Fu, YuNa; Sun, Heng; Wang, YaNi; Zheng, Ping; Xia, Feng; Wang, JianHua (Frontiers in Medicine, 2023)
Background The objective of this study is to elucidate the prevalence of systemic circulating tumor cells (CTCs) prior to and following resection of hepatocellular carcinoma (HCC), and to compare the disparities in postoperative CTCs in terms of quantity and classifications between the open liver resection (OPEN) and laparoscopic liver resection (LAP) cohorts. Patients, materials, and methods From September 2015 to May 2022, 32 consecutive HCC patients who underwent laparoscopic liver resection at Southwest Hospital were retrospectively enrolled in this study. The clinicopathological data were retrieved from a prospectively collected computer database. Patients in the OPEN group matched at a 1:1 ratio with patients who underwent open liver resection during the study period on age, gender, tumor size, number of tumors, tumor location, hepatitis B surface antigen (HBsAg) positivity, alpha-fetoprotein (AFP) level, TNM and Child-Pugh staging from the database of patients to form the control group. The Can-Patrol CTC enrichment technique was used to enrich and classify CTCS based on epithelial-mesenchymal transformation phenotypes. The endpoint was disease-free survival (DFS), and the Kaplan–Meier method and multiple Cox proportional risk model were used to analyze the influence of clinicopathological factors such as total CTCs and CTC phenotype on prognosis. Results The mean age of the 64 patients with primary liver cancer was 52.92 years (23–71), and 89.1% were male. The postoperative CTC clearance rate was more significant in the OPEN group. The total residual CTC and phenotypic CTC of the LAP group were significantly higher than those of the OPEN group (p = 0.017, 0.012, 0.049, and 0.030, respectively), which may increase the possibility of metastasis (p = 0.042). In Kaplan–Meier analysis, DFS was associated with several clinicopathological risk factors, including Barcelona Clinical Liver Cancer (BCLC) stage, tumor size, and vascular invasion. Of these analyses, BCLC Stage [p = 0.043, HR (95% CI) =2.03(1.022–4.034)], AFP [p = 0.007, HR (95% CI) =1.947 (1.238–3.062)], the number of positive CTCs [p = 0.004, HR (95% CI) =9.607 (2.085–44.269)] and vascular invasion [p = 0.046, HR (95% CI) =0.475 (0.22–1.023)] were significantly associated with DFS. Conclusion In comparison to conventional OPEN technology, LAP technology has the capacity to augment the quantity of epithelial, mixed, and mesenchymal circulating tumor cells (CTCs). Following the surgical procedure, there was a notable increase in the total CTCs, epithelial CTCs, and mixed CTCs within the LAP group, indicating a potential drawback of LAP in facilitating the release of CTCs.